STAPHYLOCOCCUS INFECTIONS IN CHILDREN - Valeriu Popescu (Amaltea Medical Publishing House, 2008)
The author presents staphylococcus infections in children with first accent about staphylococcal pneumonia (epidemiology, - pathogenicity and pathology; clinical manifestations; laboratory and roentgenographic findings; diagnosis and differential diagnosis; complications; prognosis and treatment) after which there are discussed other diseases due to staphylococcus: scalded-skinstaphylokoken (SSSS)(Ritter disease, Lyell syndrome, staphylococcal scarlet fever, bullous impetigo), staphylococcal osteomyelitis, staphylococcal enterocolitis, staphylococcal food poisoning, staphylococcal endocarditis, staphylococcal tracheitis, toxic shock syndrome (TSS).